Air Pollution During Pregnancy and Cord Blood Immune System Biomarkers. Issue 10 (October 2016) - Ashley-Martin, Jillian; Lavigne, Eric; Arbuckle, Tye E.; Johnson, Markey; Hystad, Perry; Crouse, Dan L.; Marshall, Jean S.; Dodds, Linda
Abstract : Objectives: We aimed to determine whether average and trimester-specific exposures to ambient measures of nitrogen dioxide (NO2 ) and particular matter (PM2.5 ) were associated with elevated cord blood concentrations of immunoglobulin E (IgE) and two epithelial cell produced cytokines: interleukin-33 (IL-33) and thymic stromal lymphopoietin (TSLP). Methods: This study utilized data and biospecimens from the Maternal-Infant Research on Environmental Chemicals (MIREC) Study. There were 2001 pregnant women recruited between 2008 and 2011 from 10 Canadian cities. Maternal exposure to NO2 and PM2.5 was estimated using land use regression and satellite-derived models. Results: We observed statistically significant associations between maternal NO2 exposure and elevated cord blood concentrations of both IL-33 and TSLP among girls but not boys. Conclusions: Maternal NO2 exposure may impact the development of the newborn immune system as measured by cord blood concentrations of two cytokines.